DEMOCRACY AND THEOLOGY: A CRITICAL ANALYSIS ON APPROPRIATION - Vazhappilly, Bilju (Asian Horizons, 2020)
To what extent have the Christian thinkers of this age made the proper appropriation of democratic components—voting rule or will of the majority in decision making, individual liberty, freedom of speech/press, equality, rule of law, equal rights, the ignoring of hereditary class distinctions, tolerance of minority views and participatory or collaborative nature of governing—in different theological fields and in Church teachings? This is the main focus of this article. In this regard, this article makes a critical evaluation on those earlier contributions in assimilating the democratic components in theological fields, etc. It also points out the possible challenges in appropriating democracy in theological endeavours today. In addition, this article unveils the original meaning of the term democracy which will accelerate the attempt to make possible ways of appropriating the democratic prepositions (of, by and for) in theological conversations and actions. Such a theology then would be a profound theology that initiates us toward a democracy ordered in a way that accords with God’s law and purposes. Besides, the typical nature of such theology would be purely based on the contextual, celebrational and ethical life of the Faithful.